Assessment of the Quality of Financial Statements of Government-Owned Enterprises in Bosnia and Herzegovina - Amira Pobrić (Acta Economica)
The subject of this paper is the assessment of the quality of financial statements of public enterprises in Bosnia and Herzegovina based on the information contained in the audit reports of the supreme audit institutions. The aim of the research is to determine how often auditors indicate that financial statements are not of satisfactory quality. Furthermore, the goal is to determine which International Accounting Standards (IAS) and International Financial Reporting Standards (IFRS) are most often violated for the purpose of accounting manipulations and distorting the picture of the real performance of these enterprises. The research was conducted on a sample of 135 audit reports related to the reporting periods from 2018 to 2022. The method of content analysis was used to collect data. The results of the research show that in over 80% of cases the auditors gave a modified audit opinion indicating that the quality of the financial statements is not at a satisfactory level. Most of the reasons for modifying the audit opinion relate to noncompliance with the provisions of IAS 1, IFRS 9, IAS 36, IAS 16, IAS 37 and IAS 2. In most cases, public enterprises manipulate accounting information by not assessing the impairment of fixed and current assets and reducing the value of this property to a recoverable amount. Because of this, the value of the assets is overestimated, the expenses are underestimated and the financial result is overestimated.